The Development of Entrepreneurship in the Romanian Rural Area: Array - Chiru, Gheorghe (Acta Universitatis Danubius. Œconomica, 2022)
The practice of entrepreneurship in the Romanian rural space represents a social, physical and cultural concept, which is in the complementarity of the urban space. A complete definition would neglect and omit at the same time the complexity of ethnomethodological factors, as well as the structural diversity, presented as a specificity that shapes its personality and transposes it into an a priori space. Entrepreneurship is a process, which is based on identifying and managing an opportunity in the business environment, in order to capitalize it. The rural environment includes agricultural land, habitats, forests, traditional crops, natural landscapes, communities and different types of territories. This space represents the incorporation of most of the resources of the national economy, for example, resources from agriculture, fish farming, forestry, tourism or raw materials for industry.